The US Beauty Industry and the Other Face of Racism towards the 21st Century African-American Women - Reguig, Khadidja (My University, 2019)
Although the formal legal codes of enslavement and segregation that stood for centuries has ended, the racist ideas rested and newer forms of racial prejudice appeared. In a supposed post racial period, new discrimination forms can be clearly seen in many fields like the beauty industry. Through products releases and advertisement campaigns, the industry defines beauty and sets its norms. Such conventional beauty standards are typically Eurocentric. It means that models should have lighter complexions, smoother hair textures and smaller noses and lips. As a reason to that, black skinned African-American women do not fit the Eurocentric beauty standards. They are marginalized from the industry. They are also deprived from any access to its products. In addition to all that, they get insulted through the language and pictures used in their advert campaigns.
Keywords: Post Racial Period - Racial Prejudice - Beauty Industry - Conventional Beauty Standards - Eurocentric Beauty Standards - African-American Women